Switching the direction of spin accumulation in the spin Hall effect of light by adjusting the optical axis of an uniaxial crystal - 唐明 周新星 肖志成 罗海陆 文双春 (Chinese physics B, 2013)
We theoretically and experimentally investigate a switchable spin Hall effect（SHE） of light in reflection near the Brewster angle at an air-uniaxial crystal interface.We find a large transverse spin splitting near the Brewster angle,whose sign can be altered by rotating the optical axis.As an analogy of the SHE in an electronic system,a switchable spin accumulation in the SHE of light is detected.We are able to switch the direction of the spin accumulation by adjusting the optical axis angle of the uniaxial crystal.These findings may give opportunities for photon spin manipulating and developing a new generation of nano-photonic devices.